THEORETICAL AND PRACTICAL PRINCIPLES OF THE TRAINING GROUP IN TEACHING CHILDREN TO SWIM (Scientific journal of the Fergana State University, 2024)
By studying the theoretical and practical foundations of the preparatory group in teaching children to swim, we presented the materials of a pedagogical experiment that allow us to objectively assess the correctness of the proposed hypothesis and determine the possibility of its use. We showed 13-14-year-old swimmers how to develop speed.